A review of lead-free solders for electronics applications. (August 2017) - Cheng, Shunfeng; Huang, Chien-Ming; Pecht, Michael
Abstract: Ever since RoHS was implemented in 2006, Sn3.0Ag0.5Cu (SAC305) has been the primary lead-free solder for attaching electronic devices to printed circuit boards (PCBs). However, due to the 3.0 wt% Silver (Ag) in SAC305, companies have been looking at less expensive solder alternatives, especially for use in inexpensive products that have short operating lives and are used in mild application conditions. This paper reviews new lead-free solder alternatives and the trends in the industry, including SnCu-based solders, SnAgCu solders with Ag content < 1.0 wt%, SnAg solders, and no-Ag low-temperature solders (e.g., SnBi-based solders). The analysis is conducted for reflow, wave, and rework conditions and for packaged and flip-chip devices.